Etnografia da luta infinita: assentamento e expulsão no Acampamento Capão das Antas (São Carlos, SP) - Savarego, Júlia Aricó (Universidade Federal de São Carlos, 2025)
This dissertation aims to ethnograph the resistance strategies of the residents of Acampamento Capão das Antas, a rural occupation fighting for Agrarian Reform located in the municipality of São Carlos, in the east-central region of the state of São Paulo, Brazil, in response to a currently suspended land repossession process. This process, which began in November 2011 and is now moving toward the establishment of a settlement, was legally grounded in environmental legislation. According to the group of residents with whom this work is conducted, the research concerns the creation of a documentary to write the history of the camp’s struggle. The methodological projections resulting in this text weave together an ethical-philosophical commitment, but also an aesthetic one, guiding the research’s execution. Thus, it makes sense to think of methodology necessarily as ethics expressed in the aesthetics of the text, which presents itself as a documentary—a ‘storytelling of the struggle.’ The documentary is simultaneously method, object, and research goal. I aspire for the text to be entangled as part of the struggle and to have its own political agency, given the understanding and commitment to the idea of writing as a world-creating practice. But, as the title of this dissertation announces, what does it mean to finish writing an endless struggle? In a context where exhaustion and depression were the most recurring themes, I raised the following problem: How can the certainty of the unattainable be precisely what keeps people fighting? The making of ‘Anthropology in and with the Endless Struggle’ initially led me to perceive a tension—and often contradictions—that, throughout the fieldwork begun in 2018, proved to be my own. From this realization, I wove oppositions into the ethnographic writing in an attempt to echo the movement of the struggle itself, such as the interdependent relationship between eviction and settlement in the current design of public policies aimed at land redistribution. This dissertation deals with the entanglements of hope and failure that mark what is a collective project: making home through land as a connector of temporalities, people, plants, and non-humans. I argue that the land struggle of the people of Acampamento Capão das Antas is not only about obtaining legal use but also about the constant work of forging bonds with the land, memory, and one another. And these bonds can only be sustained through care—for and with the land and the people, living and dead. It is because there are ‘affective bonds’ that people choose to stay or leave, and the affect involved is not just love and hope but also its relationship with pain and failure. This movement is echoed in this ethnography as a trigger for building comparative and imaginative bridges, enhancing life and projecting other possible futures.
Ethnography of an endless struggle: settlement and eviction in the Capão das Antas Camp (São Carlos, SP)
Keywords: Antropologia na luta infinita; Acampamento; Assentamento; Expulsão; Legislação ambiental; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL